2023
DOI: 10.15252/embj.2023114889
|View full text |Cite
|
Sign up to set email alerts
|

Structure and mechanism of a eukaryotic ceramide synthase complex

Tian Xie,
Qi Fang,
Zike Zhang
et al.

Abstract: Ceramide synthases (CerS) catalyze ceramide formation via N‐acylation of a sphingoid base with a fatty acyl‐CoA and are attractive drug targets for treating numerous metabolic diseases and cancers. Here, we present the cryo‐EM structure of a yeast CerS complex, consisting of a catalytic Lac1 subunit and a regulatory Lip1 subunit, in complex with C26‐CoA substrate. The CerS holoenzyme exists as a dimer of Lac1‐Lip1 heterodimers. Lac1 contains a hydrophilic reaction chamber and a hydrophobic tunnel for binding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…In addition, while this manuscript was under review, the cryo-EM structure of yeast Lac1p bound to an acyl-CoA was reported. That structure revealed a small lateral opening in Lac1p adjacent to the active site 56 . This observation led the authors to hypothesize that it could potentially correspond to the entry route for sphingoid base substrates 56 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, while this manuscript was under review, the cryo-EM structure of yeast Lac1p bound to an acyl-CoA was reported. That structure revealed a small lateral opening in Lac1p adjacent to the active site 56 . This observation led the authors to hypothesize that it could potentially correspond to the entry route for sphingoid base substrates 56 .…”
Section: Discussionmentioning
confidence: 97%
“…That structure revealed a small lateral opening in Lac1p adjacent to the active site 56 . This observation led the authors to hypothesize that it could potentially correspond to the entry route for sphingoid base substrates 56 . However, this lateral opening is not present in our cryo-EM structures of CerS6 or in our molecular dynamics simulations.…”
Section: Discussionmentioning
confidence: 97%